2021
DOI: 10.3390/atmos12091189
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the El Niño Southern Oscillation on the Number of Visitors to Natural Attractions: The Moderating Effect of Disposable Personal Income, per Capita GDP and Population

Abstract: Analyzing the impact of El Nilo Southern Oscillation (ENSO) on the number of tourists is essential in realizing the sustainable development of natural scenic spots. From the current research results, research on the effects of ENSO on tourism focuses on the impact of the formation of the natural environment. However, there is a lack of ENSO-related research on the number of people arriving at natural attractions. This paper considers the adjustment effects of personal disposable income, per capita GDP, and pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Similarly, only a few studies have focused on its impact on marine ecosystems [25]. Xiong et al [26] lamented the scarcity of research in this area and found that the El Niño drought decreased visits to national parks in the USA. Droughts caused by El Niño commonly lead to a decline in gross domestic product (GDP), reducing disposable income and hindering people's mobility.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, only a few studies have focused on its impact on marine ecosystems [25]. Xiong et al [26] lamented the scarcity of research in this area and found that the El Niño drought decreased visits to national parks in the USA. Droughts caused by El Niño commonly lead to a decline in gross domestic product (GDP), reducing disposable income and hindering people's mobility.…”
Section: Introductionmentioning
confidence: 99%